2011
DOI: 10.1590/s0100-204x2011001200014
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos de um Latossolo Amarelo sob diferentes sistemas de manejo

Abstract: Resumo -O objetivo deste trabalho foi avaliar os atributos químicos de um Latossolo Amarelo sob diferentes sistemas de manejo do solo, no cerrado piauiense. Foram avaliados quatro sistemas de manejo: plantio convencional por três anos; plantio direto por três anos (PD3) e cinco anos (PD5), com uso de milheto como cultivo de cobertura; e plantio direto por nove anos (PD9), dos quais sete com uso de milheto e dois com forrageira. Utilizou-se área de cerrado nativo como referência. As amostras do solo foram colet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
3
7
0
8
Order By: Relevance
“…In this management system, fertilizers and correctives are applied without incorporation, a fact that contributes both to reduce the contact surface between soil particles and products (corrective and/ or fertilizers) as to restrict the effect of these practices on most superficial layers. Similar results were reported by Campos et al (2011), who detected the accumulation of exchangeable bases within 0.0-0.10 m layer soil under NTS when assessing changes in chemical attributes of a Xanthic Ferralsol under different management systems in the Cerrado of Piauí State. Larger V values in the surface layer of a soil under NTS had also reported by Carvalho et al (2007).…”
Section: +supporting
confidence: 87%
See 1 more Smart Citation
“…In this management system, fertilizers and correctives are applied without incorporation, a fact that contributes both to reduce the contact surface between soil particles and products (corrective and/ or fertilizers) as to restrict the effect of these practices on most superficial layers. Similar results were reported by Campos et al (2011), who detected the accumulation of exchangeable bases within 0.0-0.10 m layer soil under NTS when assessing changes in chemical attributes of a Xanthic Ferralsol under different management systems in the Cerrado of Piauí State. Larger V values in the surface layer of a soil under NTS had also reported by Carvalho et al (2007).…”
Section: +supporting
confidence: 87%
“…Among them, the highest pH values (p ≤ 0.05) were observed in NTS3 and NTS6 at 0.0-0.10 m depth (Table 3). Matias et al (2009) andCampos et al (2011) also observed an increase in pH in the surface layer in areas under no-tillage. Contrarily, at 0.10-0.20, 0.20-0.30, and 0.30-0.40 m depth, the highest pH values were reached in soils under EU, being attributed to its higher OM amounts ( , K + and others within the residue NTS3: no-tillage system for three years, NTS6: no-tillage system for six years, NTS9: no-tillage system for nine years, PA2: pasture for two years, PA6: pasture for six years, EU6: eucalyptus plantation for six years, EU12: eucalyptus plantation for 12 years, CTS2: conventional tillage system for two years, CTS8: conventional tillage system for eight years, NC: native Cerrado.…”
Section: Resultsmentioning
confidence: 86%
“…2014 DOI: 10.1590/S0100-204X2014000800007 abril de 2012, isso ocorreu logo depois da colheita do milho realizada. Segundo Campos et al (2011), nessa época, o solo apresenta menor temperatura e maior umidade que no verão. Portanto, a taxa de mineralização do C orgânico do solo pode ser menor no período que antecede à primeira amostragem, o que favorece seu acúmulo em relação à segunda.…”
Section: Resultsunclassified
“…Entretanto, como a aveia-preta estava em pleno vigor vegetativo quando foi dessecada, por ocasião da amostragem, havia raízes parcialmente decompostas e seu conteúdo de C foi recuperado na análise, o que também pode ter contribuído para aumentar os teores de C orgânico especificamente nesse estágio. A variação no estoque de C orgânico entre épocas de coleta durante o ano também foi observada por Campos et al (2011) e foi relacionada à maior presença de resíduos de raízes das culturas e à ocorrência de períodos com maior umidade do solo, os quais conferiram maior estoque do que a média.…”
Section: Resultsunclassified
“…O teor de matéria orgânica na área de lavoura de cana-de-açúcar foi maior do que no solo sob cerrado, em todas as épocas avaliadas (Tabela 2 A elevação da matéria orgânica do solo favorece a capacidade de troca catiônica nos solos (Araújo et al, 2007;Campos et al, 2011), e esse efeito é mais pronunciado para RQs (Frazão et al, 2008;Carneiro et al, 2009), onde a predisposição ao processo de lixiviação de cátions e à perda da MO é maior. Porém, os teores de matéria orgânica e de CTC foram baixos tanto no RQ Lavoura quanto no RQ Cerrado (Tabela 2).…”
Section: Resultsunclassified